Macrofinancial Linkages : Trends, Crises, and Policies - Crowe, Christopher (International Monetary Fund, 2010)
Macrofinancial linkages have long been at the core of the IMF's mandate to oversee the stability of the global financial system. With the advent of the economic crisis, the Fund has drawn on this research in order to contribute to critical debates on the nature of appropriate policy responses at both the national and multilateral levels. The current juncture offers a good opportunity to take stock of this body of research by IMF staff and to share it with a wider audience, particularly since few collections have been published in this area. This volume brings together some of the best writing by IMF economists on macrofinancial issues, and highlights the issues and approaches that have guided IMF thinking in an area that makes up an increasingly important component of the IMF's overall remit. The chapters in the volume fit into three broad themes: financial crises and boom-bust cycles; financial integration, financial liberalization, and economic performance; and policy issues relating to macroeconomic policy and the corporate and financial sectors-including domestic and external financial liberalization.